Handbook of Consumer Finance Research - Xiao, Jing J. (Springer New York : Imprint: Springer, 2008)
Debt consolidation...pension givebacks...Social Security under siege...bankruptcies and foreclosures...Americans' financial lives are fraught with issues, challenges, and potential threats, in record numbers. The Handbook of Consumer Finance Research surveys the social aspects of consumer behavior, offering latest data and original research on current consumer needs as well as identifying emerging areas of research. This accessible volume (which can be read without advanced training in the field) starts with current concepts of risk tolerance, consumer socialization, and financial well-being, and moves on to salient data on specific settings and populations, including: Healthcare spending and retirement savings. Online shopping and e-banking. Family finances: marriage, parent/child communications, student spending. Financial concerns of special groups: minorities, seniors, the poor. Management issues of business-owning families. Consumer protection in fair lending. Given the current climate of rising debt and negative savings, the Handbook is timely and instructive reading for educators, researchers, and policymakers who wish to develop or evaluate financial education programs, design research initiatives, and understand better how to help families with the economic problems of our times. It can also serve as a graduate text in economics, finance, consumer science, business, and family studies.